Power amplifier for software defined radio - Dahlan, Samat. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This project investigates the characteristics of three types of Power Amplifier (PA) circuit that will use in the Software Defined Radio (SDR). The circuits are Conventional PA, the proposed PA using NPN transistor, and the proposed PA using NMOS transistor. In additio n, the circuit will be constructing with efficiency - boosting technique circuit that is using Doherty Amplifier. The simulation of the circuit will be done by using the PSpice version 9.2 simulation software. The analysis will be done by manipulating the op erating frequency that is suitable for Global System for Mobile Communication (GSM) application. The comparison that will be analyzed is the efficiency of the circuit and the output gain. The outcome of the results shows that the PA circuit using the NMOS t ransistor give high efficiency and gain. With the addition of the Doherty amplifier also has increased the performance of the circuit.